Like a Bride Adorned - Mollett, Margaret (2008)
Launching into her study of metaphor in John's Apocalypse, Lynn Huber recalls that as early as the third century, readers debated on how to interpret Revelation and whether or not it was worth interpreting. One of the primary things she sees as prompting this debate was the symbolic or imagistic nature of this text. "As the narrative account of a mystical vision, which includes a trip into the heavenly realm to view future events, Revelation consists of countless fantastic images. These images - multiwinged-beasts, scarlet dragons, furious angels among other things - are simply not part of the day to day reality experienced by humans. As a result, interpreters have continually struggled with how to understand these images : Are they to be understood literally, read symbolically, or do they function as some sort of code?" To this day, says Huber, readers have not reached a consensus regarding the method for interpreting the various images recorded in John's Revelation.
Keywords: Rezension